Synthesis, structure and properties of new triiron(III) complexes: Phosphodiester cleavage and antioxidant activity. (1st October 2022) - Durigon, Daniele C.; Duarte, Laura; Fonseca, Jessica; Tizziani, Tiago; R. S. Candela, Dalber; Braga, Antonio L.; Bortoluzzi, Adailton J.; Neves, Ademir; Peralta, Rosely A.
Graphical abstract: Herein we synthesize and fully characterized two asymmetrical phenol-based ligands containing pendant chalcogenated arms and their triiron (III) complexes. Both complexes are able to hydrolyze the 2, 4-BDNPP substrate at significant rates and show remarkable radical scavenging activity. Abstract: This paper describes the synthesis, structural and spectroscopic characterizations of two new trinuclear iron(III) complexes: [Fe3 (LS )(μ –OH)2 (μ -OAc)2 ]ClO4 (CS ) and [Fe3 (LSe )(μ –OH)2 (μ -OAc)2 ]ClO4 (CSe ) with two new phenol-based ligands containing chalcogen atoms (S or Se) in pendant arms. Both iron complexes were characterized using the following techniques: X-ray crystallography, elemental analysis, IR, Mossbauer and UV–vis spectroscopies, conductimetric analysis and mass spectrometry. The crystal structures of the complexes reveal that their coordination center is formed by three linearly arranged iron atoms, joined by μ -hydroxo, μ -phenoxo and μ -acetato bridges. The hydrolytic activity in the phosphate diester cleavage of CSe and CS was investigated using 2, 4-BDNPP as a substrate, and applying the Michaelis-Menten approach, giving the kinetic parameters (CSe /CS ): k cat (s −1 ) = 3.81 × 10 -3 /2.32 × 10 -3 and a catalytic efficiency of E =  k cat / KM, (L/mol s −1 ) = 1.83/3.18. The complexes and ligands also showed antioxidant activity.